Acute exacerbation of COPD: Physiotherapy practice and factors that influence management - Motheo Phalatse-Taban; Heleen van Aswegen (South African Journal of Physiotherapy)
Background: Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is a leading cause of morbidity and mortality in South Africa. Physiotherapy practice and factors that influence management of patients with AECOPD are unknown.